The Westminster concise Bible dictionary - Smith, Barbara, 1922-; Wright, G. Ernest (George Ernest), 1909-1974 (Philadelphia : Westminster Press, 1981)
Defines terms and identifies persons, places, and objects mentioned in the Bible. Also includes references to Biblical passages, maps, and a time line.
First published under title: Young people's Bible dictionary.
"Westminster historical maps of Bible lands, edited by G. Ernest Wright and Floyd V. Filson": p. [163]-[172]
Includes map index.
Bibliography: p. 161.
Keywords: Bible -- Dictionaries